A case of sporadic Peutz-Jeghers syndrome presenting as multiple intussusceptions. Issue 3 (9th March 2022) - Gorji, Leva; Huish, Grant; Morgan, Joshua; Levy, Paul
Abstract: Peutz-Jeghers syndrome (PJS) is an autosomal dominant mutation of the STK11/LKB1 gene on chromosome 19 often characterized by mucocutaneous pigmentation, hamartomatous polyps, anemia, gastrointestinal bleeding and intussusception. We present the case of a 21-year-old female with no pertinent family history who received the diagnosis of PJS after presenting to the hospital with two episodes intussusception. Patients with PJS have an increased lifetime risk of developing stomach, small bowel, colon, pancreatic, breast, cervical, uterus and testicular cancer requiring religious surveillance at an early age.